Proceedings of the 3rd International Conference on Computer Graphics, Virtual Reality, Visualisation and Interaction in Africa 2004
DOI: 10.1145/1029949.1029978
|View full text |Cite
|
Sign up to set email alerts
|

A local model of eye adaptation for high dynamic range images

Abstract: In the real world, the human eye is confronted with a wide range of luminances from bright sunshine to low night light. Our eyes cope with this vast range of intensities by adaptation; changing their sensitivity to be responsive at different illumination levels. This adaptation is highly localized, allowing us to see both dark and bright regions of a high dynamic range environment. In this paper we present a new model of eye adaptation based on physiological data. The model, which can be easily integrated into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 33 publications
1
58
0
1
Order By: Relevance
“…Edge-stopping filters limit such spatial processing to the regions with homogeneous pixel intensity, which greatly reduces the halo artifacts, but also ignores glare due to bright pixels in the proximity of high-contrast edges. The spatial support of such filters is typically fixed [Ledda et al 2004;Kuang et al 2007] (e.g., to 2% of the image size) or adaptively expanded as a function of the local variability in pixel intensities [Reinhard et al 2002].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Edge-stopping filters limit such spatial processing to the regions with homogeneous pixel intensity, which greatly reduces the halo artifacts, but also ignores glare due to bright pixels in the proximity of high-contrast edges. The spatial support of such filters is typically fixed [Ledda et al 2004;Kuang et al 2007] (e.g., to 2% of the image size) or adaptively expanded as a function of the local variability in pixel intensities [Reinhard et al 2002].…”
Section: Related Workmentioning
confidence: 99%
“…For example, the Naka-Rushton response was originally derived as a function of adaptation state for single receptors [Naka and Rushton 1966;Valeton 1983], but its variants are commonly used for larger adaptation areas, sometimes the entire image, without any in-depth justification [Tumblin et al 1999;Pattanaik et al 2000;Irawan et al 2005;Ledda et al 2004;Reinhard et al 2002;Kim et al 2009;Reinhard and Devlin 2005]. In this work, we propose a perceptually grounded model of local adaptation that accounts for the spatial configuration of HDR pixels, and we show that its use can be beneficial in many different applications (Section 7).…”
Section: Related Workmentioning
confidence: 99%
“…11 According to Knoblauch et al, a large contrast in luminance increases visual recognition, 12 whereas the continuity of the contrast has contributed to visual discomfort. 5 Therefore, human vision provides a time-dependent adaptation 11,13,14 to reduce visual fatigue. Some studies have also revealed that the maximum luminance contrast between text and background is inadequate for reading a display because an excessively high contrast leads to visual stress.…”
Section: Introductionmentioning
confidence: 99%
“…The global tone mapping method using only one mapping function has a relatively simple computation, though it is insufficient to address wide dynamic range, whereas the local tone mapping method has an adaptive function that may vary depending on spatially adjacent pixels. Furthermore, certain local methods adopt human visual properties for local contrast enhancement, such as image color appearance model (iCAM)-based methods, 3,4 logarithmic mapping, 5 local eye adaptation, 6 and histogram adjustment. 7 These make images similar to real scenes that an observer would perceive.…”
Section: Introductionmentioning
confidence: 99%